Preparation of hyperbranched polystyrene-g-poly(N-isopropylacrylamide) copolymers and its application to novel thermo-responsive cell culture dishes. (23rd July 2015) - Sudo, Yu; Sakai, Hideaki; Nabae, Yuta; Hayakawa, Teruaki; Kakimoto, Masa-aki
Abstract: This paper describes the preparation of hyperbranched polystyrene- g -poly( N -isopropylacrylamide) (HBPSt- g -PNIPAM) and its application as a novel thermo-responsive material for cell sheet preparation. HBPSt- g -PNIPAM was synthesized by grafting PNIPAM from the termini of HBPSt via reversible addition fragmentation transfer polymerization. The resulting HBPSt- g -PNIPAM was cast from a solution onto a commercial polystyrene-based dish (PS-dish) to make a thermo-responsive surface for cell cultivation (P4/PS-dish). Mouse 3T3 fibroblast cells were seeded on the P4/PS-dish with 2.5–3.5 μg/cm 2 of PNIPAM and cultured at 37 °C for four days to achieve high confluency. Fairly large cell sheets were successfully collected by cooling the dish to 20 °C. The current material avoids the use of electron beam polymerization, which requires complicated equipment, for fabricating a thermo-responsive surface because PNIPAM is immobilized by the affinity between the hyperbranched polystyrene segment and the PS-dish. Graphical abstract: Highlights: Copolymers of hyperbranched polystyrene and poly( N -isopropylacrylamide) (HBPSt- g -PNIPAM) have been successfully synthesized. The structure of HBPSt- g -PNIPAM is flexibly tunable by changing reaction conditions. Thermo-responsive cell culture dishes can be easily prepared by casting HBPSt- g -PNIPAM on commercial polystyrene dishes. The prepared thermo-responsive dishes demonstrate promising results in fabricating cell sheets of mouse 3T3 fibroblast cells.